POLA PENCEMARAN Hg DAN Pb PADA FISHING GROUND DAN IKAN YANG TERTANGKAP NELAYAN : STUDI KASUS DI TELUK JAKARTA (Mercury and Lead Contamination Pattern on Fish and Fishing Ground : A Case Study in Jakarta Bay) - Mustaruddin, Mustaruddin (Bumi Lestari; Vol 13 No 2 (2013), 2013)
Abstract Mercury (Hg) and lead (Pb) are two heavy metals which run-off with waste water of industry, market, and office to territorial water of Jakarta Bay. Fishing ground in adjacent water of Marunda, Bidadari Island, and Damar Island have been contaminated by Hg and Pb. Pelagic fish caught in Jakarta Bay have not been contaminated by Hg and Pb. However, demersal fishes that have been caught in the same area, a positively contaminated with Hg and Pb. The rate of Hg and Pb in fishing ground are signicantly influence by the rate of Hg and Pb in pelagic fish (NK Hg = 0,895 at sig 0,016 and NK Pb = 0,962 at sig 0,002) and in demersal fish (NK Hg = 0,825 at sig 0,043 and NK Pb = 0,894 at sig 0,016). The pattern of Hg contamination in fishing ground to pelagic fish and demersal fish each following linear model Y = -0,055 + 5,314 X, and quadratic model Y = -1,370 + 215,549X – 4190,579X2, where X represents rate of heavy metal in fishing ground and Y represents rate of heavy metal in fish caught by fisherman. While pattern of Pb contamination of fishing ground to pelagic fish and demersal fish each following cubic model Y = -0,006 +1,114X - 399,652X3 and sigmoid model Y = e0,627 – (0,10 / X).
Keywords: Keywords: fishing ground, fish, heavy metal, contamination, and Jakarta Bay